A general way to assign IPv6 trusted address under portal authentication - Jiang ZHOU; Hewu LI (Dianxin kexue)
As the network scale grows,it is especially important to fine-tune the network.In the next-generation Internet,embedding the user's trusted identity into the IPv6 address suffix to assign trusted addresses can further improve the traceability of network behavior.At present,many studies have attempted to embed the user’s identity information into IPv6 addresses based on portal authentication and DHCPv6,but the modification of DHCPv6 makes it not transparent to the terminal.A mechanism for trusted address assignment in IPv6 networks based on portal authentication was proposed.The collaboration between servers and software-defined networking (SDN) technology was used to realize the indirect assignment of IPv6 trusted addresses.Finally,a prototype system was implemented and its feasibility and performance were evaluated in the network of Nanjing Telecom in Jiangsu.The results show that the mechanism only brings little overhead and it is transparent to the terminal.